2003
DOI: 10.1093/ndt/gfg1040
|View full text |Cite
|
Sign up to set email alerts
|

The role of arterial hypertension in the progression of non-diabetic glomerular diseases

Abstract: Arterial hypertension (AH) per se is, together with diabetes mellitus, the most important cause of renal failure and of dialysis in the western world. AH is also a well known consequence of chronic renal disease, and at the same time one of the main factors which causes diabetic and/or non-diabetic chronic renal failure progression. AH is mostly registered in patients with focal segmental glomerulosclerosis and with membranoproliferative glomerulonephritis. The pathophysiology and the mechanism of AH within pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 6 publications
2
23
0
1
Order By: Relevance
“…The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A significant increase in the prescription of ARBs was observed in 2003 compared with 1996 in RD patients.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A significant increase in the prescription of ARBs was observed in 2003 compared with 1996 in RD patients.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have suggested that the combined treatment with ACE inhibitors and ARBs may be more renoprotective than treatment with either agent alone (12,(20)(21)(22)24), and, indeed, in some RD patients, the combination of ACE inhibitors and ARBs was also prescribed in the present study. The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, sodium retention, volume expansion, and reduced synthesis of vasodilator substances subsequent to the rise in BP may exacerbate hypertension. Impairment of autoregulation of glomerular pressure may also lead to glomerular hypertension (20). Given that activation of the renin-angiotensin-aldosterone system not only causes a rise in BP, but also promotes cell proliferation, inflammation, and matrix accumulation, it may also lead to the progression of CKD (17).…”
Section: Discussionmentioning
confidence: 99%
“…Some possible explanations for this may be the different model and the different starting time of atRA administration. Because hypertension is a risk factor for the progression of renal diseases [34] , a decrease in hypertension underlies the renoprotective effects of atRA.…”
Section: Wwwchinapharcom Liu X Et Almentioning
confidence: 99%